1977
DOI: 10.1084/jem.145.5.1278
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of primary responses to the IgG class and dependency of IgM responses on secondary immunization for the copolymers of L-glutamic acid, L-tyrosine, and L-alanine.

Abstract: Primary responses to the linear polymers of L-glutamic acid, L-tyrosine, and L-alanine are restricted to the IgG class of antibodies. The appearance of specific IgM antibodies against these antigens is dependent upon secondary immunization, in contrast to many classical antigenic systems. The presence of an IgM response was verified by a direct plaque-forming cell assay, the inhibition of direct plaques by an antiserum specific for mouse micron-chain, and the physical separation of IgM and IgG GAT-specific ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Preliminary experiments showed that BALB/c mice made very strong primary antibody responses to FγG, but rather weak responses to the DNS hapten. We previously reported (45,46) that boosting mice with antigen 3-5 d after the initial antigen priming would result in a robust antibody response. In the experiments reported here, groups of 5 BALB/c mice were fed SD, LCD, or LED30 and remained on the diets throughout the experimental protocol.…”
Section: Immunization For Antibody Responsesmentioning
confidence: 99%
“…Preliminary experiments showed that BALB/c mice made very strong primary antibody responses to FγG, but rather weak responses to the DNS hapten. We previously reported (45,46) that boosting mice with antigen 3-5 d after the initial antigen priming would result in a robust antibody response. In the experiments reported here, groups of 5 BALB/c mice were fed SD, LCD, or LED30 and remained on the diets throughout the experimental protocol.…”
Section: Immunization For Antibody Responsesmentioning
confidence: 99%